A Remark on the Blowup of Solutions to the Laplace Equations with Nonlinear Dynamical Boundary Conditions. (11th August 2010) - Zhang Zhang, Hongwei Hongwei; Hu Hu, Qingying Qingying
Abstract : We present some sufficient conditions of blowup of the solutions to Laplace equations with semilinear dynamical boundary conditions of hyperbolic type.